Testing the efficient market hypothesis : an event study approach - Demko, Roman (2021)
The Efficient Market Hypothesis (EMH) is one of the most famous economic concepts and the fundamental cornerstone of modern financial theory. It is the topic where several subjects intersect, such as corporate finance, behavior finance, economic theory, investment management, accounting, psychology, history, physics, and probably much more. Such interrelation of different areas in one phenomenon is what makes it so attractive to study. Theoretical concepts and market application of the EMH are combined in the thesis. The sense of the EMH may be shortly stated as a condition under which the prices reflect all available information. Its principle is simple, but it is not easy to check it in real life. Even though the paper title implies testing the efficient market hypothesis, any tests associated with it are approximate, as the hypothesis is very theoretical. The goal of this paper is twofold: firstly, to build a solid theoretical foundation of the EMH, market anomalies that violate it, and behavioral biases; secondly, to investigate how the Dutch stock market has been reacted to earnings releases during the last ten years, using the event study methodology. The last part of the paper focuses on the possible trading strategy that can be applicable under the condition that the EMH is partially held.